Basic neurochemistry : principles of molecular, cellular, and medical neurobiology - Siegel, George J.; Albers, R. Wayne (Robert Wayne); Price, D. L. (Donald Lowell); Brady, Scott T.; ScienceDirect eBooks (Amsterdam : Academic Press, 2012)
Basic Neurochemistry: Principles of Molecular, Cellular, and Medical Neurobiology, the outstanding and comprehensive classic text on neurochemistry, is now newly updated and revised in its Eighth Edition. For more than forty years, this text has been the worldwide standard for information on the biochemistry of the nervous system, serving as a resource for postgraduate trainees and teachers in neurology, psychiatry, and basic neuroscience, as well as for medical, graduate, and postgraduate students and instructors in the neurosciences. The text has evolved, as intended, with the science. It is.
Brain endothelial cells restrict the transport of many substances while permitting essential molecules access to the brainThere are multiple transporters and transport processes for bidirectional transport at the BBB; Lipid solubility is a key factor in determining the permeability of a substance through the BBB by passive diffusion; The BBB expresses solute carriers to allow access to the brain of molecules essential for metabolism; Receptor-mediated transcytosis (RMT) is the primary route of transport for some essential peptides and signaling molecules.
Includes bibliographical references and index.
ATP-binding cassette transporters (ABC) on luminal membranes of the BBB restrict brain entry of many molecules.
Elsevier
Keywords: Neurochemistry; Neurochemistry; Nervous System Diseases; Nervous System Physiological Phenomena; MEDICAL -- Neuroscience; PSYCHOLOGY -- Neuropsychology; Neurochemistry; Neurochemie; Electronic books